Sacrocolpopexy with polyvinylidene fluoride mesh for pelvic organ prolapse: Mid term comparative outcomes with polypropylene mesh. (January 2018) - Balsamo, Raffaele; Illiano, Ester; Zucchi, Alessandro; Natale, Franca; Carbone, Antonio; Sio, Marco De; Costantini, Elisabetta
Abstract: Objective: The aim of this study was to compare the surgical, anatomical, and functional outcomes of sacrocolpopexy (SCP) using polyvinylidene fluoride (PVDF) mesh versus SCP using the standard polypropylene (PP) mesh. Study design: This was a retrospective single centre case-control study including female patients who underwent laparoscopic or abdominal SCP for POP with either PP (Cousin Biotech ® ) or PVDF (DynaMesh ® -PRS) mesh between March 2005 and May 2015. Anatomical outcomes were assessed by the Pelvic Organ Prolapse Quantification (POP-Q) system. Functional outcomes included voiding and storage urinary symptoms (VS and SS, respectively), urgency and stress urinary incontinence (UUI and SUI) and sexual dysfunction (SD). Symptoms and their impact on patients' quality of life (QoL) were assessed using validated questionnaires as Incontinence Impact Questionnaire (IIQ-7), Urinary Distress Inventory (UDI-6) and Female Sexual Function Index (FSFI). Global patient perception of improvement (PGI-I questionnaire) and mesh erosion rates were also recorded. Results: Of the 166 patients enrolled, 136 could be included in the analysis: 73 in the PP group and 63 in the PVDF group. The mean follow-up was 94± 17.31 months for the PP and 25.6± 13.8 months for the PVDF group. There were no statistically significant differences in patient demographics and preoperative clinical characteristics. Postoperative anatomical correction were not significantly different between the two groups. The PVDF group showed superior results in term of storage symptoms (PVDF = 0% versus PP = 8.2%; p = 0.02) and lower rate of sexual dysfunction (PVDF = 0% versus PP = 16, 4%; p = 0.001). Only 1 patient in PP group and 2 in PVDF group (p = 0.47) presented a mesh exposure. There was no statistical difference in PGI-I scores (PP = 1.5 ± 1.0 vs PVDF = 1.8 ± 0.5; p = 0.40). Conclusions: Our findings suggest that both meshes can be safely and effectively used with good anatomical outcomes. Interestingly, PVDF use was associated with significantly less storage symptoms and sexual dysfunction.